Role of Indonesia’s G20 Presidency and Exchange Rate on LQ45 stock price: Dynamic Panel Model Approach - Rahayu, Caecilia Wahyu Estining; Rahmawati, Christina Heti Tri; Wuri, Josephine; Hardanti, Yuliana Rini; Harnoto, Laurentius Bambang (Migration Letters, 2024)
This study investigates the role of Indonesia’s G20 presidency and exchange rates on the stock prices of LQ45. Daily data were collected from companies listed on Indonesia’s stock exchanges between November 15 and December 24, 2022. Furthermore, we employed a dynamic panel model approach, specifically the system generalized method of moments regression. This analytical technique controls for unobserved heterogeneity, simultaneity, and dynamic endogeneity. The results illustrate that Indonesia’s G20 presidency positively impacts the stock prices in LQ45. In addition, Exchange rate negatively influences on the LQ45 stock prices, and the stock prices of LQ45 in the previous year often correspond to that in the current year. This study’s results provide recommendations for potential investors who wish to invest in the subsectors of LQ45 member companies. The policies implemented during Indonesia’s G20 presidency can increase stock prices and create positive market sentiment to encourage migration flows. Additional studies are required to determine the impact of implementing the G20 priority agenda, which includes enhancing the global health framework, fostering employment prospects, transitioning to green and renewable energy, and advancing the digital economy to increase stock prices.